2021
DOI: 10.5194/acp-21-1835-2021
|View full text |Cite
|
Sign up to set email alerts
|

Effects of thermodynamics, dynamics and aerosols on cirrus clouds based on in situ observations and NCAR CAM6

Abstract: Abstract. Cirrus cloud radiative effects are largely affected by ice microphysical properties, including ice water content (IWC), ice crystal number concentration (Ni) and mean diameter (Di). These characteristics vary significantly due to thermodynamic, dynamical and aerosol conditions. In this work, a global-scale observation dataset is used to examine regional variations of cirrus cloud microphysical properties, as well as several key controlling factors, i.e., temperature, relative humidity with respect to… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
23
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 17 publications
(26 citation statements)
references
References 80 publications
3
23
0
Order By: Relevance
“…Since no INP measurements were provided by the AWARE campaign, acquiring additional observations of INPs in the future are recommended for this remote region in order to quantify the impacts of various types of INPs over Antarctica. Another study showed that the simulated IWC and ice crystal mean diameter in CAM6 are underestimated compared with in situ observations, possibly due to weaker aerosol indirect effects and insufficient amounts of ice particle growth in the model (Patnaude et al., 2021). Therefore, to increase ice mass concentration and the amount of supercooled liquid water, further modifications are recommended for CNT, CLUBB and MG2 parameterizations, INP number concentrations and ice particle growth.…”
Section: Discussion and Summarymentioning
confidence: 99%
See 1 more Smart Citation
“…Since no INP measurements were provided by the AWARE campaign, acquiring additional observations of INPs in the future are recommended for this remote region in order to quantify the impacts of various types of INPs over Antarctica. Another study showed that the simulated IWC and ice crystal mean diameter in CAM6 are underestimated compared with in situ observations, possibly due to weaker aerosol indirect effects and insufficient amounts of ice particle growth in the model (Patnaude et al., 2021). Therefore, to increase ice mass concentration and the amount of supercooled liquid water, further modifications are recommended for CNT, CLUBB and MG2 parameterizations, INP number concentrations and ice particle growth.…”
Section: Discussion and Summarymentioning
confidence: 99%
“…A threshold of 10 −4 was applied to model cloud fraction output as the limit of in‐cloud condition. In addition, in‐cloud condition in the simulation also needs to satisfy CWC > 10 −7 g m −3 , which is a typical limit used for defining in‐cloud condensed water mass concentrations in GCMs (e.g., Patnaude et al., 2021).…”
Section: Observational and Simulation Data Setmentioning
confidence: 99%
“…Therefore, the sum of simulated ice and snow mass concentrations for a specific size range (i.e., 0-5,000 μm in this study) is used to compare with the observed IWC derived from measurements of a similar size range. A similar method was previously used in several model-observation comparison studies, such as Fridlind et al (2007), Eidhammer et al (2014), and Patnaude et al (2021). Table S1 in Supporting Information S1 shows the contributions of various discrete size ranges of ice and snow to their mass concentrations in the CAM6 simulation.…”
Section: Approaches To Facilitate Comparisons Between Model Simulations and Observationsmentioning
confidence: 99%
“…SCAM RCE also exhibits time-mean saturation over ice (RH ≥ 100) near the tropopause. While ice supersaturation is frequently observed by aircraft (e.g., Patnaude et al, 2021) as well as in satellite data (e.g., Gettelman et al, 2006), and occurs in the RCE simulations of other single column models, cloud-resolving models, and large eddy simulations (Figure 8 in Wing et al [2020]), its prevalence in the grand mean is an artifact of the strict single column geometry: in 3D RCE with CAM5 and CAM6, dry regions make the space-time mean unsaturated (Figure 3 in Reed et al [2021]). In the lower-middle troposphere, mean RH profiles all hover near the 60%-80% range, with SAM being the outlier, on the humid side.…”
Section: Simulations With 300-k Sstmentioning
confidence: 99%